The Influence of Online Shopping Applications on The Welfare of Traders in The Sungguminasa Traditional Market Area - Ruma, Zainal (Economics and Business Journal (ECBIS), 2023)
This research investigates the impact of using online shopping applications on the welfare of traditional market traders in the Sungguminasa Traditional Market area. This study explores changes in business patterns, income, and living conditions of traditional market traders as a result of the penetration of online shopping applications. The research methods used include surveys, and interviews, to measure the extent to which online shopping applications influence their well-being. The results of this research provide valuable insight into economic and social changes in traditional markets due to continuously developing digital technology.